2012
DOI: 10.1099/ijs.0.035592-0
|View full text |Cite
|
Sign up to set email alerts
|

Idiomarina aquimaris sp. nov., isolated from the reef-building coral Isopora palifera

Abstract: A bacterial strain designated SW15T was isolated from a sample of the reef-building coral Isopora palifera, collected in southern Taiwan. The novel strain was characterized using a polyphasic taxonomic approach. Cells of strain SW15 T were Gram-negative, aerobic, light yellow, rod-shaped and motile by means of a single polar flagellum. In phylogenetic analyses based on 16S rRNA gene sequences, strain SW15 T appeared to belong to the genus Idiomarina in the class Gammaproteobacteria and to be most closely relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…The fatty acid profiles of strain TS-T11 T and the three reference type strains are shown in . The cellular fatty acid profiles obtained in this study for the reference type strains were similar to those originally reported (Jean et al , 2006; Park et al , 2010; Yoon et al , 2007) and reported in other publications (Chen et al , 2012; Song et al , 2013; Taborda et al , 2009) in terms of major fatty acids. All these strains contained iso-C 15 : 0 , iso-C 17 : 0 and iso-C 17 : 1 ω9 c as major fatty acids, although in different proportions, which might be due to the different culture conditions.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…The fatty acid profiles of strain TS-T11 T and the three reference type strains are shown in . The cellular fatty acid profiles obtained in this study for the reference type strains were similar to those originally reported (Jean et al , 2006; Park et al , 2010; Yoon et al , 2007) and reported in other publications (Chen et al , 2012; Song et al , 2013; Taborda et al , 2009) in terms of major fatty acids. All these strains contained iso-C 15 : 0 , iso-C 17 : 0 and iso-C 17 : 1 ω9 c as major fatty acids, although in different proportions, which might be due to the different culture conditions.…”
supporting
confidence: 90%
“…Similar polar lipid profiles were shown with the three reference type strains. The polar lipid profiles obtained in this study for I. salinarum DSM 21900 T and I. taiwanensis CGMCC 1.12292 T were similar to those described previously (Chen et al , 2012). All of strain TS-T11 T and the three reference type strains had PE, PG, DPG and five uncharacterized phospholipids (PL1–PL5).…”
supporting
confidence: 87%
“…The description is identical to that given for Idiomarina homiensis by Kwon et al (2006) . Additional characteristics are as follows: the polar lipids comprise PE, PG, DPG, phosphatidylserine (PS), an uncharacterized aminolipid (AL1) and eight uncharacterized PLs (PL1-PL8) ( Chen et al, 2012 ). The type strain is PO-M2 T ( = KACC 11514 T = DSM 17923 T ), which was isolated from seashore sand in Pohang, Korea.…”
Section: Discussionmentioning
confidence: 99%
“…is not a typical representative of the marine waters around Helgoland. It has been isolated from various marine environments such as deep-sea waters, hydrothermal vents, sediments, and reef building corals (e.g., Ivanova et al, 2000 ; Donachie et al, 2003 ; Chen et al, 2012 ; Zhang et al, 2012 ), but also from estuarine environments like Baltic Sea surface water (Brettar et al, 2003 ). The increased occurrence of these two OTUs at Helgoland Roads during the first half of the sampling period (group A), leads to the hypothesis that OTUs that are commonly associated with coastal marine environments have been passively transported to Helgoland Roads with the above mentioned coastal water inflow.…”
Section: Discussionmentioning
confidence: 99%